2017
DOI: 10.1016/j.jalz.2017.07.754
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E4 inhibits autophagy gene products through direct, specific binding to CLEAR motifs

Abstract: ApoE4-CLEAR interactions may account for suppressed autophagy in APOE ɛ4/ɛ4 carriers and, in this way, contribute to earlier AD onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 45 publications
1
81
0
Order By: Relevance
“…Our results provide evidence of the AD relevance of risk genes, but it is also important to identify the regulatory elements and transcriptional factors that regulate the expression of these genes for molecular dissection of disease etiology [45, 46]. Recent study have shown that APOEε4 genotype suppress transcription of autophagy mRNA’s by competing with transcription factor EB for binding to coordinated lysosomal expression and regulation(CLEAR) DNA motifs [47]. TFs were identified for each module with high normalized enrichment scores (NES ≥ 4) from iRegulon (Methods), which correspond to an estimated false discovery rate of less than 0.01 [33] (Supplemental Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Our results provide evidence of the AD relevance of risk genes, but it is also important to identify the regulatory elements and transcriptional factors that regulate the expression of these genes for molecular dissection of disease etiology [45, 46]. Recent study have shown that APOEε4 genotype suppress transcription of autophagy mRNA’s by competing with transcription factor EB for binding to coordinated lysosomal expression and regulation(CLEAR) DNA motifs [47]. TFs were identified for each module with high normalized enrichment scores (NES ≥ 4) from iRegulon (Methods), which correspond to an estimated false discovery rate of less than 0.01 [33] (Supplemental Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Lamp2 expression is up-regulated by MCS, which is involved in fusing the lysosome to the autophagosome to facilitate autophagy (88). Lamp2 is decreased in AD apolipoprotein E4/E4 brains, potentially driving early onset AD pathology (89). Ppt1, which is up-regulated by MCS, has been linked to both endosomal dysfunction and increased apoptotic pathway activity in neuronal ceroid lipofuscinosis (90).…”
Section: Discussionmentioning
confidence: 99%
“…A third, independent connection between Alzheimer pathology and TFEB function was reported with the observation that TFEB binding to the promoters of lysosomal genes can be outcompeted by apolipoprotein E4 (apoE4) (Parcon et al . ). ApoE4 is the protein encoded by the APOE ɛ4 allele, the single greatest genetic risk factor for the development of Alzheimer's disease (Strittmatter and Roses ).…”
Section: Impaired Tfeb Signaling In Neurodegenerative Diseasementioning
confidence: 97%
“…In vitro, apoE4 could bind to DNA probes carrying the CLEAR motif with much greater affinity than apoE3, the protein product of APOE ɛ3 allele which is not a risk factor for Alzheimer's disease; increased apoE4 binding to CLEAR probes was paralleled by decreased TFEB binding to the same probes, and expression of apoE4 diminished the expression of TFEB target genes (Parcon et al . ). Thus, several independent pathways seem to converge to disturbed TFEB‐mediated lysosomal biogenesis as a potential common leitmotif in the pathogenesis of Alzheimer's disease.…”
Section: Impaired Tfeb Signaling In Neurodegenerative Diseasementioning
confidence: 97%